Legal Aspect on Indonesia Military-Industrial Complex to Strengthening Defence Industry Research and Clasterization in Building Independent Defence Industry in Indonesia - Baiquni, Muhammad Iqbal; Rafikawati, Yulia Fajar; Indah, Wulan Saputri; Arifin, Ridwan; Nte, Ngboawaji Daniel (Indonesian Journal of Advocacy and Legal Services, 2022)
Indonesia's bitter experience of the embargo became a hard slap and a reminder of the importance of the National Defense Industry in meeting the needs of the TNI's defense equipment and encouraging the quality of the TNI's performance in carrying out the territorial defense of the Republic of Indonesia. Over time the development of the National Defense Industry continues to grow and is supported by regulations at the level of the Law, namely Law no. 16 of 2012 concerning the Defense Industry in realizing the Independence of the National Defense Industry. However, over time the implementation of Law no. 16 of 2012 does not work properly, challenges and problems arise, there are two problems in the National Defense Industry, namely Research and Development (R&D) and Defense Clustering. In this paper, a deeper review of the complex defense industry uses the research method, namely normative juridical research with two approaches including the statute approach and the conceptual approach. The results of the research in this paper carry the Core Indonesia Military-Industrial Complex which supports the strengthening of Research by initiating the Concept of Feedback and Clustering of the Defense Industry by forming 7 Defense Industry Clusters which include Raw Material Industry, Production Industry, Assembly Industry, Production, Support Industry (Components, Spare Parts), Electronic Industry, Maintenance.